Salvianolic acid A (Sal A) suppresses malignant progression of glioma and enhances temozolomide (TMZ) sensitivity via repressing transgelin-2 (TAGLN2) mediated phosphatidylinositol-3-kinase (PI3K) / protein kinase B (Akt) pathway. Issue 5 (2nd May 2022) - Ye, Tingting; Chen, Rongrong; Zhou, Yu; Zhang, Juan; Zhang, Zhongqin; Wei, Hui; Xu, Yan; Wang, Yulan; Zhang, Yinlan
ABSTRACT: Glioma originated from excessively proliferative and highly invaded glial cells is a common intracranial malignant tumor with poor prognosis. Resistance to temozolomide (TMZ) is a clinical challenge in glioma treatment due to the fact that chemoresistance remains a main obstacle in the improvement of drug efficacy. Salvianolic acid A (Sal A), originated from traditional Chinese herbal medicine Salvia miltiorrhiza, possesses anti-tumor effects and could facilitate the delivery of drugs to brain tumor tissues. In the present work, effects of Sal A on the viability, proliferation, migration, invasion and apoptosis of human glioma cell line U87 cells as well as influence of Sal A on TMZ resistance were measured, so as to identify the biological function of Sal A in the malignant behaviors and chemoresistance of glioma cells. Additionally, activation of TAGLN2/PI3K/Akt pathway in glioma cells was also detected to investigate whether Sal A could regulate TAGLN2/PI3K/Akt to manipulate the progression of glioma and TMZ resistance. Results discovered that Sal A treatment reduced the viability, repressed the proliferation, migration and invasion of glioma cells as well as promoted the apoptosis of glioma cells. Besides, Sal A treatment suppressed TAGLN2/PI3K/Akt pathway in glioma cells. Sal A treatment strengthened the suppressing effect of TMZ on glioma cell proliferation and reinforced the promoting effect of TMZ on glioma cell apoptosis, which were abolished by upregulation of TAGLN2. To conclude, Sal A treatment could suppress the malignant behaviors of glioma cells and improve TMZ sensitivity through inactivating TAGLN2/PI3K/Akt pathway. Graphical Abstract: uf0001